Antibacterial Activity of Methanol Extract of Sargassum polycystum on Escherichia coli and Staphylococcus aureus - Mursal Ghazali; Muhammad Zaki; Ernin Hidayati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Macroalgae is a commodity that is used as food, medicine, fertilizer and other materials in industries. Macroalgae in the medical world have the potential to be anticancer, antiviral, antifungal and antibacterial. One type of macroalgae that has the potential as an antibacterial source is Sargassum polycystum. This study aims to analyze the ability of the methanol extract of S. polycystum to inhibit the growth of bacteria (Escherichia coli and Staphylococcus aureus) and analyze the potential compounds contained in the methanol extract of S. polycystum. This research is an experimental study using a completely randomized design. Extraction method by maceration. The test concentrations used were 20%, 40%, 60%, 80%, positive and negative control. While the test method uses a good diffusion method. Data were analyzed using description and SPSS application. The results showed that the methanol extract of S. polycystum had better inhibition against S. aureus growth than E. coli. The methanol extract concentration of S. polycystum, which had the best inhibition against S. aureus and E. coli was 80%. Metabolites content on S. polycystum extract is Tetradecanoic Acid, Loliolide; Hexadecanoid Acid, Methyl Ester, 9-Hexadecanoid Acid, Hexadecenoic Acid, 8-Octadecanoic, Methyl Ester, 5,8,11,14-Eicosatetraenoic Acid and Ethyl Ester.